Implementation of the Development of Islamic Religious Education through Religious Habituation Activities to Strengthen the Profile of Pancasila Students at MTsN Gresik - Khoirul Amin; Abdul Muid; Khoirul Faizin (Institut Attanwir Bojonegoro, 2024)
One of the benchmarks used to determine the quality of graduates in the Independent Curriculum is the Pancasila Student Profile. The significance of this research lies in the relevance of religious habituation activities, which are used as a medium for PAI development to strengthen the Pancasila Student Profile, as well as to determine its impact in forming lifelong student characters who are competent, have character and behave by Pancasila values. This research analyses the efforts and effects of developing PAI through religious habituation activities to strengthen the Pancasila Student Profile. This research adopts a qualitative method with a case study approach. Data collection techniques include interviews, observation and documentation. Data analysis was done through data reduction, presentation, and conclusion. Verification of data validity is guaranteed through credibility, dependability and confirmability tests. Efforts to develop PAI through religious habituation activities start from the stage: planning, including analyzing ideas, preparing programs and building joint commitment; implementation, including socialization and program implementation; evaluation, including observations, monitoring instruments and coordination with parents; and follow-up is carried out through evaluation meetings and follow-up programs. The strategies used include structural, formal, mechanical, and organic. There are vertical and horizontal forms of activity. Meanwhile, the development impacts are students able to interpret and apply religious morals, personal morals, morals among others, and morals in nature; students become more familiar with and appreciate various cultures, improving communication and interaction between students from different cultural backgrounds; students are more able to collaborate, show concern, and have a sense of wanting to share; students can increase self-understanding of the situations they face and develop self-regulation; make students more active in searching for and processing information and ideas; and students can produce original ideas, works and actions.